Application of Tiab's Direct Synthesis technique to multi-layer naturally fractured reservoirs. - Owayed, Jalal Farhan. (My University, 2000)
Next, the problem of the pressure behavior of a well crossed by a uniform-flux and infinite-conductivity vertical fracture and located in a single-layer and multilayered bounded square reservoir with a double porosity system is studied. The type curves obtained for the infinite-conductivity fracture are qualitatively the same as the uniform-flux solutions. Only the shape is slightly different at intermediate times. For the case of uniform-flux vertical fracture, type curves show the existence of three flow regimes: (1) the linear flow line of slope 0.5, (2) infinite-acting radial flow line of a horizontal straight line, and (3) pseudo-steady state flow line of slope unity, in addition to the transition region. The infinite-conductivity vertical fracture case reveals a fourth dominated flow regime which can be identified by a straight line of slope 0.36. This flow period is called the bi-radial flow. Unfortunately, the infinite-acting flow period is dominant only if xex f > 8. It was found that the effect of flow capacity ratio is the major factor on the pressure derivative curves during the late time pseudo-steady state.

The development of the Tiab's Direct Synthesis procedure for a commingled multi-layer infinite-acting, naturally fracture reservoir is examined. In this work, a new set of type curves are developed for both transient and pseudo-steady state flow including wellbore storage and skin. It is important to note that the shapes of either pressure or pressure derivative curves for the layered reservoir are similar to those of a single-layer reservoir. New empirical correlations are developed to solve for the flow capacity in each layer. A very important observation is that for l1l1 < 100, the derivative curve has two depressions. It is concluded from this study that the peak points on pressure derivative curves are more affected by wellbore storage than by skin.

From fluid loss during drilling to simulation and completion design to reservoir characterization; understanding of the unique reservoir behavior of multi-layered systems is required in both homogeneous and double-porosity reservoirs. Pressure analysis theory becomes complicated in a multilayer reservoir where several layers are communicating through the wellbore only.
Keywords: Oil wells Hydraulic fracturing.; Oil wells Testing.; Oil reservoir engineering.; Engineering, Petroleum.; Petroleum engineering.